SAT0503 Can balneotherapy modify microrna expression levels in osteoarthritis? a comparative study in patients with knee osteoarthritis treated with mud-bath therapy. (15th June 2017) - Giannitti, C; Palma, A De; Cheleschi, S; Facciolo, J; Pascarelli, NA; Galeazzi, M; Fioravanti, A
Abstract : Background: MicroRNAs (miRNAs) are a class of 19–23 nucleotides long non-coding RNAs that post-transcriptionally regulate the activity of target mRNAs. MicroRNAs are involved in cartilage homeostasis and play an important role in the pathogenesis of osteoarthritis (OA). They have been detected in human plasma and in synovial fluid and are considered as potential diagnostic biomarkers and therapeutic targets of OA. Balneotherapy is a common non-pharmacological treatment for OA patients. In a previous published prospective single-blind randomized clinical trial in patients with knee OA, we showed that a cycle of mud-bath therapy (MBT) in addition to conventional treatments induced an improvement on pain, functional capacity and quality of life in comparison to standard treatment alone. Objectives: as part of this study we evaluated the whole blood levels of miR-155, 223, 181a, 146a and miR-let-7e, which are involved in the pathogenesis of OA. Methods: Thirty-two patients aged between 50 and 75 years with knee OA defined by the ACR criteria were included for the current analysis, based on the availability of blood sample at basal time and after 2 weeks. Twenty-one patients (MBT group) were daily treated with a combination of daily local mud-packs at 42°C and baths in mineral water, at 37°C for 15 min, for a total of 12 applications over a period of 2 weeks, in addition to standard therapy; the other eleven patients (control group) continued their conventional treatment alone. Clinical parameters [global pain score by a 0–100 mm Visual Analog Scale (VAS); physical function, total pain score and total stiffness score (WOMAC)] and microRNAs expression were performed at basal time and after 2 weeks. Peripheral whole blood was collected into PAXgeneTM Blood RNA tubes and then stored a -80°C. Total RNA was extracted using the PAXgeneTM Blood miRNA kit and the relative expression of miR-146a, miR-155, miR-223, miR-181a and miR-let-7e were determined by qRT-PCR. Results: At the end of MBT we observed a statistically significant improvement of clinical paramethers. Furthermore, we observed a significant decrease of miR-155, 181a and miR-146a (p<0.001) and of miR-223 (p<0.01) expression levels. On the contrary, no clinical and biochemical modifications were detected in the control group. Concerning miR-let-7e expression levels no significant variations were showed in both groups after 2 weeks. Conclusions: Our data showed that MBT can modify the expression levels of miR-155, 181a, 146a and 223 expression levels, that are up-regulated in OA. This MBT effect could be explained considering the role of the heat stress and of the hydrostatic pressure, since some miRNAs were found to be temperature and mechano-responsive. Further studies are needed to better explain the mechanism of action of MBT and the role of miRNAs in OA. References: Cheleschi S et al. Int J Mol Sci. 2017. De Palma A et al. Clin Exp Rheumatol. 2017. Fioravanti A et al. Int J Biometeorol. 2015. Potla R. et al. RNA. 2015. Disclosure of Interest: None declared